Financial system performance in European Union countries: do country’s governance indicators matter? - Barbu, Teodora Cristina; Boitan , Iustina Alina (Journal of Business Economics and Management, 2020)
The study analyses the impact of country’s governance factors on the financial behaviour and performance of financial intermediaries operating in European Union countries, by covering the period 2000–2017. Empirical evidence provided by the paper relies on a set of financial and political factors that has not been previously studied. Four indicators are jointly used as proxies for capturing the various dimensions of a country’s good governance, while 21 financial indicators represent the alternative dependent variables meant to comprehensively depict the banking sector and capital market development. Each panel regression has been controlled for country’s degree of economic development and its membership to OECD and euro-zone. The findings indicated that various dimensions of political factor caused different effects on financial sector features. Control of corruption, solid political and economic stability determine significant effects on most financial variables considered (almost two-thirds of the financial indicators considered). Even after controlling for the lagged effect of governance factors the main results hold, in that monitoring corruption, maintaining political stability and designing sound economic policies still have an impact on most financial indicators considered. Another interesting conclusion supported by the results is that not all political instability indicators are detrimental for banking and stock market functioning.